Long-term trend and spatiotemporal variations of haze over China by satellite observations from 1979 to 2013. (October 2015) - Zhang, Xingying; Wang, Ling; Wang, Weihe; Cao, Dongjie; Wang, Xi; Ye, Dianxiu
Abstract: With the fast development of economy and industry in the past thirty years, many large cities in the eastern and southwestern areas of China are experiencing increased haze events and atmospheric pollution, which causes significant impacts on the regional environment, human health, and even climate. The long-term trend and spatiotemporal variations of haze over China during recent 30 years are investigated using TOMS AAI products. In addition, the heavy haze events that occurred in January 2013 over eastern China are explored using AAI products from TOU on board FY-3A. Validation results show that satellite AAI products can be used for haze monitoring since it is sensitive to the carbonaceous aerosol, which is one of the main components of haze. In China, the high AAI values (>1.0) mainly located in the main four areas with intense anthropogenic activities, except for the desert region in Northwestern China. In the eastern and northeastern region, AAI peaks dominate in spring before 2005 since those areas were always affected by dust in spring. However, after 2005, AAI peaks appear in winter over eastern China because of haze. Moreover, in the northeastern region, AAI peaks dominate in winter with a secondary peak in spring because this area is affected by both dust and haze. In the southern region, the AAI peaks always dominate in spring since the high-level air pollution often occur in spring, but a decreasing trend is acquired during recent ten years. Over eastern China and northeastern China, AAI shows an increasing trend during recent 30 years in winter, which reveals that the haze over these areas is strengthen. A case study result shows that the heavy haze events occurred in January 2013 in eastern China can be clearly identified from the AAI products of TOU/FY-3A. The daily coverage area with AAI > 3.0 peaks at five periods at this time, i.e. Jan. 7–8, Jan. 13, Jan. 18, Jan. 23, and, Jan. 28–29, which agrees well with the haze events recorded by in-situ measurements. Highlights: Long-term observation of haze in China by satellite. Satellite AAI products are demonstrated to be used in haze monitoring in China. Haze shows significant increase over east and northeast of China in recent ten years.